2019
DOI: 10.1101/574152
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pan-GWAS of Streptococcus agalactiae highlights lineage-specific genes associated with virulence and niche adaptation

Abstract: Streptococcus agalactiae (Group B streptococcus, GBS) is a coloniser of the gastrointestinal and urogenital tracts in adults, and an opportunistic pathogen of infants and adults. The worldwide population of GBS is characterised by a series of Clonal Complexes (CCs) with different invasive potentials. CC17 for example is commonly associated with neonatal sepsis and meningitis, while CC1 often causes invasive disease in adults with co-morbidities. The genetic basis of GBS virulence and to what extent different C… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Microbial GWAS approaches can be particularly powerful, when pan-genomic variation of closely related bacterial strains can be leveraged, as has been shown for e.g. virulence genes [75]. We showed that genetic variation between the strains P1C6b, DSM2003, DSM2343, and DSM3504 (mean ANI = 95.5%) empowered us to pinpoint the TBP ( Figure S1).…”
Section: Microbial Gwas For Host Traits Can Benefit From Strain Levelmentioning
confidence: 58%
“…Microbial GWAS approaches can be particularly powerful, when pan-genomic variation of closely related bacterial strains can be leveraged, as has been shown for e.g. virulence genes [75]. We showed that genetic variation between the strains P1C6b, DSM2003, DSM2343, and DSM3504 (mean ANI = 95.5%) empowered us to pinpoint the TBP ( Figure S1).…”
Section: Microbial Gwas For Host Traits Can Benefit From Strain Levelmentioning
confidence: 58%
“…4A). The Pan-GWAS approach helped identify genes unique for each clade which could be considered contributing to virulence and/or niche adaptation (26).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically it is useful for identifying outbreak strains, which is a major use of MinION sequencing (error-prone Nanopore reads). In a recent paper [49] the authors worked on almost 2000 samples of Streptococcus agalactiae, characterized by different degrees of virulence and preferred host. However, even if the microbiologists are demanding regarding the distinction of strains, they only distinguish a few dozen different types at most.…”
Section: Discussionmentioning
confidence: 99%